Peningkatan Keterlibatan Pengguna dalam Deteksi Alergi Makanan Melalui Design UI/UX dan Gamifikasi - Rezon Handry Gunawan; Sulaeman Santoso (Journal of Smart Technology and Engineering, 2025)
Abstract — This research discusses the development of the Foodlergic application which aims to increase user engagement in detecting food allergens through the application of gamification and designing a more attractive user interface (UI/UX). This application uses image scanning technology to identify food ingredients that have the potential to trigger allergies, so that it can help users in maintaining the safety of daily food consumption. However, this application still has some shortcomings, such as dependence on internet connection and unattractive interface design. To overcome this, the development of gamification features in the form of a point and level system, as well as UI/UX improvements were carried out to increase motivation and frequency of use of the application. The development method focused on building an Android-based application and implementing a comprehensive gamification system—including points, levels, and leaderboards—utilizing Firebase to manage user authentication, data synchronization, and the core gamification logic. The results showed that the application of gamification and UI/UX design improvements were able to increase user engagement and consistency in using the application. These findings suggest that the integration of gamification approach and good interface design can be an effective strategy in increasing public awareness of the dangers of food allergens and encouraging the prevention of adverse effects caused by food allergies.